Spatial variance of organic matter respiration stoichiometry in the Arctic Ocean ... - Gerace, Skylar; Chung-Swanson, Tia; Fagan, Adam; Brock, Melissa; Cooper, Lee; Danielson, Seth; Ashjian, Carin; Grebmeier, Jacqueline; Martiny, Adam (Dryad, 2025)
This dataset supports the findings and conclusions presented by Gerace et al. in "Spatial variance of organic matter respiration stoichiometry in the Arctic Ocean." The data was measured from seawater samples collected aboard the US Coast Guard Cutter Healy as part of a Synoptic Arctic Survey cruise (HLY2202/AWS2022). The cruise started at Port of Dutch Harbor, Unalaska, Alaska on 4 Sept. 2022, went up to the geographic North Pole (90°N), and then returned to Dutch Harbor on 24 Oct. 2022. Variables of interest featured in this dataset include particulate chemical oxygen demand (PCOD), organic carbon (POC), organic nitrogen (PON), temperature, salinity, nutrients, light availability, dissolved oxygen, and ice coverage. Included as well are the relative frequencies of plankton taxonomic compositions and gene modules (KEGG) from DNA sampling and short-read metagenomic sequencing. ... : # Spatial variance of organic matter respiration stoichiometry in the Arctic Ocean (Dataset S1) Dataset DOI: [10.5061/dryad.8gtht7710](10.5061/dryad.8gtht7710) ## Description of the data and file structure We deployed a Sea-Bird Electronics 9/11 Conductivity, Temperature, and Depth (CTD) system fitted with a rosette of 24 Niskin bottles (10 L capacity). Conductivity (SBE 4C), temperature (SBE 3+), dissolved oxygen (SBE 43), and photosynthetic active radiation (PAR, Biospherical QSP 2350) were directly measured throughout the water column. We estimated values for every tenth degree of latitude and longitude and 1 dbar of pressure. We recorded the interpolated value at 10 dbar and 50 dbar to represent the surface and subsurface waters, respectively, for each station. Sea surface temperature was also measured by the underway system and recorded for 110 out of 113 stations and was used to confirm the accuracy of the interpolated data points. Seawater was collected by the Niskin bottles for determining ...